Digitalization of the Judiciary and Its Impact on Criminal Procedure Law Reform - Haning, Semuel; Latianingsih, Nining; Budiyanto, Budiyanto; Wilsa, Wilsa; Putri, Vegitya Ramadhani (Yayasan Baru Haji Samsudin, 2026)
The digitalization of the judiciary has significantly transformed criminal justice systems worldwide, introducing both efficiency and new legal challenges. This research explores the impact of judicial digitalization on criminal procedure law, specifically focusing on how digital technologies affect procedural practices, legal safeguards, and fundamental rights. The study aims to identify key areas where criminal procedure law must be reformed to accommodate digital practices without compromising fairness, transparency, and due process. Using a library-based research method, this study analyzes relevant literature, legal texts, and case studies to assess the implications of digital tools such as virtual hearings and digital evidence management. Findings indicate that while judicial digitalization enhances efficiency and access to justice, it also creates legal uncertainties, particularly concerning data privacy, digital evidence handling, and the protection of defendants' rights. The research concludes that comprehensive legal reform is necessary to align criminal procedure law with the realities of digital justice, ensuring that technological advancements contribute to, rather than undermine, fair and transparent criminal proceedings.